Lessons from COVID‐19: A reflection on the strengths and weakness of early consensus recommendations for pediatric difficult airway management during a respiratory viral pandemic using a modified Delphi method. Issue 10 (26th August 2021) - Stein, Mary Lyn; Park, Raymond S.; Afshari, Arash; Disma, Nicola; Fiadjoe, John E.; Matava, Clyde T.; McNarry, Alistair F.; von Ungern‐Sternberg, Britta S.; Kovatsis, Pete G.; Peyton, James M.
Abstract: Background: The authors recognized a gap in existing guidelines and convened a modified Delphi process to address novel issues in pediatric difficult airway management raised by the COVID‐19 pandemic. Methods: The Pediatric Difficult Intubation Collaborative, a working group of the Society for Pediatric Anesthesia, assembled an international panel to reach consensus recommendations on pediatric difficult airway management during the COVID‐19 pandemic using a modified Delphi method. We reflect on the strengths and weaknesses of this process and ways care has changed as knowledge and experience have grown over the course of the pandemic. Recommendations: In the setting of the COVID‐19 pandemic, the Delphi panel recommends against moving away from the operating room solely for the purpose of having a negative pressure environment. The Delphi panel recommends supplying supplemental oxygen and using videolaryngoscopy during anticipated difficult airway management. Direct laryngoscopy is not recommended. If the patient meets extubation criteria, extubate in the OR, awake, at the end of the procedure. Reflection: These recommendations remain valuable guidance in caring for children with anticipated difficult airways and infectious respiratory pathology when reviewed in light of our growing knowledge and experience with COVID‐19. The panel initially recommended minimizing involvement of additional people and trainees and minimizing techniques associated with aerosolization of viral particles. The demonstrated effectiveness of PPE and vaccination at reducing the risk of exposure and infection to clinicians managing the airway makes these recommendations less relevant for COVID‐19. They would likely be important initial steps in the face of novel respiratory viral pathogens. Conclusions: The consensus process cannot and should not replace evidence‐based guidelines; however, it is encouraging to see that the panel's recommendations have held up well as scientific knowledge and clinical experience have grown.